TEKNIK PERANTAIAN UNTUK KETERAMPILAN BERPAKAIAN PADA ANAK TUNAGRAHITA SEDANG - Rusdi Rusli; Istiqomah Istiqomah; Jehan Safitri (JIP (Jurnal Intervensi Psikologi), 2022)
Children with moderate intellectual disabilities experiencing obstacles in academics, reading, and arithmetic, but can be educated to take care of themselves. One of the important adaptive behaviors for individuals to master is dressing skills and these skills can be improved by modifying behavior. This study aims to determine the effectiveness of the application of the chaining technique in improving dressing skills in children with moderate mental retardation. The sampling technique in this study used purposive sampling with the criteria of children aged 6-11 years, experiencing problems in intellectual function in the IQ range of 35-55 (Binet's scale), inhibited in adaptive function, and unable to dress independently. Data collection techniques in this study used observation and interviews. The results indicate that there is a change in the level of dress skills in children with intellectual disabilities in the moderate category before and after applying the chaining technique.